2008
DOI: 10.1037/0097-7403.34.3.375
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons perceive the Ebbinghaus-Titchener circles as an assimilation illusion.

Abstract: A target circle surrounded by larger "inducer" circles looks smaller, and one surrounded by smaller circles looks larger than they really are. This is the Ebbinghaus-Titchener illusion, which remains one of the strongest and most robust of contrast illusions. Although there have been many studies on this illusion in humans, virtually none have addressed how nonhuman animals perceive the same figures. Here the authors show that the Ebbinghaus-Titchener figures also induce a strong illusion in pigeons but, surpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 42 publications
(74 reference statements)
1
81
1
Order By: Relevance
“…In support of this explanation, Rosa Salva et al (2013) implemented a more naturalistic training and testing protocol and found that 4-day-old chicks were susceptible to the Ebbinghaus illusion in the same direction as humans, contradictory to findings in six-month-old chickens by Nakamura et al (2008Nakamura et al ( , 2014. Further investigation into potential factors responsible for the different findings is required.…”
Section: Does Visual (Mis)perception Differ Across Ecological Niches?mentioning
confidence: 84%
See 2 more Smart Citations
“…In support of this explanation, Rosa Salva et al (2013) implemented a more naturalistic training and testing protocol and found that 4-day-old chicks were susceptible to the Ebbinghaus illusion in the same direction as humans, contradictory to findings in six-month-old chickens by Nakamura et al (2008Nakamura et al ( , 2014. Further investigation into potential factors responsible for the different findings is required.…”
Section: Does Visual (Mis)perception Differ Across Ecological Niches?mentioning
confidence: 84%
“…Moreover, Nakamura, Watanabe, and Fujita (2008) found that pigeons appeared to experience an opposite illusion, perceiving the circle surrounded by large inducer circles to be larger than the circle surrounded by small inducer circles. In a size classification task, these pigeons judged a target circle surrounded by large inducers to be larger than its true size and a target circle surrounded by small inducers to be smaller than its true size.…”
Section: Comparison Of Findings For the Ebbinghaus Ponzo And Müllermentioning
confidence: 99%
See 1 more Smart Citation
“…Baboons do not experience the illusion (Parron & Fagot, 2007) despite showing other visual illusions (e.g., Barbet & Fagot, 2002;Benhar & Samuel, 1982). This might suggest human-uniqueness in seeing this illusion, as would the reported reversed Ebbinghaus-Titchener illusions in pigeons (Nakamura, Watanabe, & Fujita, 2008) and bantam chickens (Nakamura, Watanabe, & Fujita, 2014). However, the story again is not that simple, as other nonprimate species have shown evidence of perceiving this illusion in the direction shown by humans (dolphin: Murayama, Usui, Takeda, Kato, & Maejima, 2012;domestic chicks: Rosa Salva, Rugani, Cavazzana, Regolin, & Vallortigara, 2013; redtail splitfin fish: Sovrano, Albertazzi, & Rosa Salva, 2015).…”
Section: Perceptual Illusionsmentioning
confidence: 90%
“…Some species demonstrate human-like susceptibility, some demonstrate no susceptibility, and some demonstrate reversed susceptibility (e.g., Agrillo, Parrish, & Beran, 2014;Fujita, 1996Fujita, , 1997Murayama, Usui, Takeda, Kato, & Maejima, 2012;Nakamura, Watanabe, & Fujita, 2008;Sovrano, Albertazzi, & Salva, 2014;Watanabe, Nakamura, & Fujita, 2011. Moreover, even within a species, mixed findings have been observed in susceptibility to the same illusion (e.g., Nakamura et al, 2008Nakamura et al, , 2014Salva, Rugani, Cavazzana, Regolin, & Vallortigara, 2013). One species in which such findings have recently been observed is the domestic dog.…”
mentioning
confidence: 98%